IMPORTÂNCIA DE MODELOS DE CONTRATAÇÃO DE PROJETOS CORPORATIVOS: ESTUDOS DE CASO - Julião, Mariana; Melhado, Silvio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Corporation's business strategies changes impact on visual communication and layout configuration to receive clients and attain talents. Architecture firms need to capture and translate the client's needs into desigb criteria and input their limits to balance client's expectation when signing a contract. This contract must have a commercial purpose, but also be used as a guide to the architecture firm to pre-design and design development, concerning deadlines, coast control, final product quality and client's satisfaction all long the project process. In many corporate project processes, architects find difficulty in attending client's needs and expectations. Reworks and scope of work changes during design phases turn out to be the most common adversities concerning the design process, overcoming gaps between project design phases and civil work execution, making professionals lose productivity and projects to be more expensive. This paper objective is to check project delivery methods in order to avoid rework, schedule delays and unforeseen costs and, therefore, uses as methodology theme related literature and case studies analysis through interview. After interview and case' scope of work analysis, the result of this research was that lack of information from client drive to scope changes and reworks.